О некоторых особенностях агентивных существительных положительной оценки - Лaссaн Э. Р. (Kalbotyra, 1988)
The present article deals with the two groups of nouns – adjectivised and primary. It is outlined that noun peculiarities are in the meaning. Their quality varies from plus to minus. The nouns or the second group have the study plus quality.